Pathways to psychiatric care and factors associated with delayed help-seeking among patients with mental illness in Northern Ethiopia: a cross-sectional study - Mubarek Abera; Senait Teshager; Habtamu Kerebih; Hailemariam Hailesilassie (BMJ Open)
Objective This study aimed to assess pathways to psychiatric care and factors associated with delayed help-seeking among patients with mental illness in Northern Ethiopia using the WHO Pathway Study Encounter Form.Design A cross-sectional study design was used.Setting Data were collected using face-to-face interview from patients with various diagnoses of mental illness attending outpatient treatment at Ayder Comprehensive Specialized Hospital in Mekelle City, Tigray, Northern Ethiopia.Participants Participants who came to attend outpatient treatment during the study period were included in the study using consecutive sampling technique.Outcome measures Pathways to psychiatric care, delayed psychiatric treatment and factors affecting delayed psychiatric treatment.Results The median duration from problem onset to contact with first care provider was 4 weeks, whereas contact with modern psychiatric services was 52.0 weeks. Study participants who were single (adjusted OR (AOR)=2.91, 95% CI 1.19 to 7.11), divorced (AOR=3.73, 95% CI 1.33 to 10.49) and who perceived mental illness as shameful (AOR=3.29, 95% CI 1.15 to 9.41) had delayed treatment-seeking behaviour, whereas participants with no history of substance use (AOR=0.43, 95% CI 0.20 to 0.92) were less likely to have delayed treatment-seeking behaviour.Conclusions There is significant delay in seeking modern psychiatric treatment. Religious healers were the first source of help for mental illness. Majority of the respondents described that mental illness was due to supernatural causes. Stigma and lack of awareness about where treatment is available were barriers to seeking appropriate care.